2008
DOI: 10.1111/j.1365-2516.2008.01798.x
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study on the effects of the transition of paediatric to adult health care in patients with haemophilia and in their parents: patient and parent worries, parental illness‐related distress and health‐related Quality of Life

Abstract: Summary.  The aim of this pilot study was to investigate the effects of the transition from paediatric to adult health care services in haemophilia patients and their parents. We compared pretransition children (n = 9) and their parents (n = 18) to posttransition patients (n = 8) and their parents (n = 21). Pre‐ and posttransition patients did not differ in self‐rated health‐related quality of life (QoL) or worries about the transition. Fathers of posttransition patients rated their son’s QoL as poorer than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
69
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(71 citation statements)
references
References 23 publications
0
69
0
2
Order By: Relevance
“…It appears to have a stronger impact on parents of patients with hemophilia than on the patients themselves (19).But our patients have not undergone this transition to adult health care facilities.…”
Section: Discussionmentioning
confidence: 96%
“…It appears to have a stronger impact on parents of patients with hemophilia than on the patients themselves (19).But our patients have not undergone this transition to adult health care facilities.…”
Section: Discussionmentioning
confidence: 96%
“…Young people have also expressed frustration at the over-involvement of parents post healthcare transition [53,54]. Parents therefore appear to be more concerned than their children about the adolescent's ability to be autonomous [35,55]. It is essential that parents understand the importance of supporting young people to develop the skills and confidence they need to effectively manage their own LTC throughout and beyond transfer to adult care [56].…”
Section: Discussionmentioning
confidence: 99%
“…Working in partnership with parents, as well as young people, will likely lead to a smoother and more effective transition for all. However, despite acknowledgement of the need for parent-targeted transition support [10,55,62] Allen et al [28] highlight that provision for parents is withdrawn at the time they need it most. Intervention studies remain limited.…”
Section: Discussionmentioning
confidence: 99%
“…The Canadian Pediatric Society issued two position statements stating paediatricians should be flexible and highlighted the importance of considering the child’s developmental age when planning transition to adult services [14,15]. Research in the Netherlands has reported studies of adolescents’ and their parents’ experiences of transition [16,17], and more recently [18] evaluation of transition programmes available and the effect of transition to adult services on young people.…”
Section: Introductionmentioning
confidence: 99%